2008
DOI: 10.1002/cjoc.200890029
|View full text |Cite
|
Sign up to set email alerts
|

A Meldrum's Acid Catalyzed Synthesis of Bis(indolyl)methanes in Water under Ultrasonic Condition

Abstract: A highly effective Meldrum's acid catalyzed synthesis of bis(indol-3-yl)methanes has been developed. This reaction provides the corresponding bis(indol-3-yl)methanes in high yields after short reaction time in the presence of 2 mol % catalyst in water under ultrasonic condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Tang and Wu [37] studied residents' satisfaction with eco-tourism development in rural communities and recognized the importance of ecology to residents. According to Wang, Lang and Na [38], destination residents, to different degrees and in different dimensions, were influenced by the destination tourism industry. Ap [39] studied residents' views on tourism impacts and proposed a social exchange process model as the theoretical basis to explore residents' perceptions of tourism impacts.…”
Section: Sociocultural Economic and Environmental Impacts On Tourismmentioning
confidence: 99%
“…Tang and Wu [37] studied residents' satisfaction with eco-tourism development in rural communities and recognized the importance of ecology to residents. According to Wang, Lang and Na [38], destination residents, to different degrees and in different dimensions, were influenced by the destination tourism industry. Ap [39] studied residents' views on tourism impacts and proposed a social exchange process model as the theoretical basis to explore residents' perceptions of tourism impacts.…”
Section: Sociocultural Economic and Environmental Impacts On Tourismmentioning
confidence: 99%
“…Under the influence of sonic waves inside the reaction vessel, there was the formation of microscopic bubbles, as a result of high temperature and pressure [28][29][30][31]. These tiny microscopic bubbles also help in the cyclization process.…”
Section: Chemistrymentioning
confidence: 99%
“…Immense application of ultrasound has been highlighted recently in organic and material science [30][31]. Ultrasound increased the rate of reaction by acoustic cavitation phenomena generated as a result of initiation, growth and collapse of bubbles during the course of reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Zeng, et al [29] have reported synthesis of BIMS catalyzed by ceric ammonium nitrate (CAN) under ultrasound irradiation. Subsequently, other ultrasound irradiation methods using aminosulfonic acid [30], meldrum's acid [31], silicotungstic acid [32] and acrylonitrile butadiene styrene (ABS) [33] were also reported. However, the catalysts used are hazardous, expensive and not easily available.…”
Section: Introductionmentioning
confidence: 99%